A hydrogel electrolyte based on hydroxypropyl methylcellulose modified polyacrylamine for efficient electrochromic energy storage devices. (15th March 2023) - Xu, Guangtao; Han, Yiying; Li, Xiaowei; Tao, Jiayu; Wei, Wang; Gu, Zhuo; Wang, Yuyao; Huang, Yuchen; Liu, Jian
Graphical abstract: We reported an electrochromic energy storage device based on a hydrogel electrolyte derived from hydroxypropyl methylcellulose modified polyacrylamine. Highlights: A new hydrogel electrolyte based on hydroxypropyl methylcellulose modified polyacrylamine was developed. The electrochromic energy storage device based on the present hydrogel electrolyte showed efficient performance. A LED can be lighted on by the present electrochemical device. Abstract: The electrolyte play a crucial role for the efficient operation of electrochemical devices. In this work, we developed a new hydrogel electrolyte based on hydroxypropyl methylcellulose modified polyacrylamine framework for electrochromic energy storage devices. By using the present electrolyte, the sandwich electrochemical devices based on complementary electrodes of prussian blue (PB) and tungsten trioxide (WO3 ) thin films exhibited reversible electrochromic switch between colorless and dark blue, with large optical contrast over 80 %, short response time below 2 s, high coloration efficiency over 168 cm 2 /C, and good cycle stability. Moreover, the devices showed good energy storage ability with an area capacitance of 6.32 mAh/m 2 at a current density of 0.02 mA/cm 2 . The dual functional electrochemical devices showed potential application in energy saving smart windows.